Corporate Governance Moderated Profitability, Liqyidity and Cash Flow on Financial Distress - Agus Munandar; Eva Triyana (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to determine the effect of Corporate Governance in moderating Profitability, Liquidity, and Cash Flow on Financial Distress. Net Profit Margin measures profitability. The Current Ratio measures liquidity. The Operating Cash Flow Ratio measures Cash Flow, and Altman Z-score measures Financial Distress. This study uses Corporate Governance as a moderating variable measured by the Board of Commissioners indicator. The sample used in this study is 156 data on manufacturing companies listed on the Indonesia Stock Exchange for 2020-2021. That year, there was an outbreak of the covid-19 pandemic that occurred almost all over the world, allowing many companies to experience financial distress problems. The hypothesis in this study was tested using multiple linear regression. The results showed that profitability had a significant positive effect on financial distress, while liquidity and cash flow had no significant effect on financial distress. Corporate governance as a moderating variable cannot strengthen the influence of Profitability, Liquidity, and Cash Flow on financial distress (Z-Score Index)